Toward a Synodal Church in Africa echoes from an African Christian palaver - Okafor, Ikenna Ugochukwu; Ngalula, Josée 1960-; Ilo, Stan Chu (Orbis Books, 2024)
"African Catholic theologians reflect on synodality and the church in Africa"--
"Originally published as Journeying Together for a Synodal Church in Africa, 2023 by St Paul Communications/Daughters of St Paul (Nairobi, Kenya)"--T.p. verso
Keywords: Catholic Church / Africa; Church renewal / Catholic Church; Councils and synods; Africa / Church history; Renouveau de l'Église / Église catholique; Conciles et synodes; Afrique / Histoire religieuse; Catholic Church; Africa; Church history